2012
DOI: 10.1111/j.1365-2966.2012.22058.x
|View full text |Cite
|
Sign up to set email alerts
|

PKS 0347+05: a radio-loud/radio-quiet double active galactic nucleus system triggered in a major galaxy merger

Abstract: We present optical, infrared (IR) and radio observations of the powerful Fanaroff–Riley type II (FR II) radio source PKS 0347+05 (z = 0.3390), and demonstrate that it is a rare example of a radio‐loud/radio‐quiet double active galactic nucleus (AGN) system, comprising a weak‐line radio galaxy (WLRG) separated by 25 kpc (in projection) from a Seyfert 1 nucleus at the same redshift. Our deep Gemini optical images show a highly disturbed morphology, with a warped dust lane crossing through the halo and nuclear re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 49 publications
(72 reference statements)
2
27
0
Order By: Relevance
“…Studies on AGN lifetime agree that it lasts between 10 5 to 10 9 years, depending what is consider to constrain the AGN activity (ratio between the number of RG/GV/SFG populations, period of X-ray being emitted by a central event, length of radio jets, statistics in function of redshift, etc). Tadhunter et al (2012) studied a dual radio-loud/radio-quiet AGN system. Through the assumption that both AGN were triggered at same time by a major galaxy merge, they observe radio emission from hot spots away from the nucleus even not observing emission from the narrow-line region of one of the AGNs.…”
Section: Stellar Mass-age Relationmentioning
confidence: 99%
“…Studies on AGN lifetime agree that it lasts between 10 5 to 10 9 years, depending what is consider to constrain the AGN activity (ratio between the number of RG/GV/SFG populations, period of X-ray being emitted by a central event, length of radio jets, statistics in function of redshift, etc). Tadhunter et al (2012) studied a dual radio-loud/radio-quiet AGN system. Through the assumption that both AGN were triggered at same time by a major galaxy merge, they observe radio emission from hot spots away from the nucleus even not observing emission from the narrow-line region of one of the AGNs.…”
Section: Stellar Mass-age Relationmentioning
confidence: 99%
“…Eventually, the scenario I propose implies an evolution from Seyfert 2s to LINERs and Seyfert 1 galaxies caused by an increase in jet production efficiency. I note that the rather clear separation of the Seyfert 2s from the rest of the sample suggests that the transition in efficiency happens relatively fast compared to the characteristic life times of galactic radio jets, meaning 10 6 years (cf., e.g., Tadhunter et al 2012).…”
Section: Inspection Ofmentioning
confidence: 99%
“…Several authors have found evidence for connection between the merger process and the AGN activity for both radio-loud and radio-quiet AGNs (e.g. Combes et al 2009;Ellison et al 2011;Ramos Almeida et al 2012;Villar-Martín et al 2012;Tadhunter et al 2012; Khabiboulline et al 2014). However, there are also studies that find no relationship between the AGN activity and mergers (e.g.…”
Section: Introductionmentioning
confidence: 99%